Corporate governance provisions, family involvement, and firm performance in publicly traded family firms - Esra Memili; Kaustav Misra (International Journal of Financial Studies, 2015)
This study examines the moderation effects of corporate governance provisions on the link between family involvement (i.e., family ownership and family management) in publicly-traded firms and firm performance by drawing upon agency theory, with a focus on principal-principal agency issues, and the extant family governance literature. We develop and test the hypotheses on 386 of the S&P 500 firms longitudinally. Findings support the hypotheses suggesting the moderation effects of the use of provisions (a) protecting controlling owners in terms of their sustainability of controlling status, and (b) protecting management legally on the inverted U-shaped relationship between family ownership and firm performance. We also found support for the moderation effects of provisions (c) protecting controlling owners in terms of their voting rights, (d) protecting noncontrolling owners, and (e) protecting management monetarily on the inverted U-shaped relationship between family management and firm performance. By this, our study provides empirical support for the principal-principal agency perspective on the corporate governance in publicly-traded family firms. As such, it suggests new avenues of research for both the corporate governance literature, as well as for the theory of the family firm. Our study also offers insights to policy directed toward monitoring the actions of large shareholders such as family and enhancing the overall shareholder value in publicly-traded family firms.
Keywords: G32; 330; corporate governance; principal-principal agency theory; governance provisions; family firms; firm performance